2023
DOI: 10.3390/su15075855
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Fundamental Concepts of Computational Thinking on Students’ Anxiety and Motivation toward K-12 English Writing

Abstract: Computational thinking (CT) skills are now a key part of everyday life and work, and CT has been incorporated into K-12 curricula worldwide. Combining the fundamental concepts of CT with English writing constitutes an innovative and sustainable learning strategy. However, few academic studies have examined the incorporation of CT into English writing. English writing frequently generates excessive stress and anxiety among students, yet motivation can mitigate the negative effect of anxiety. This study investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Therefore, improving these skills is of high urgency, as relying on technology without mastering its underlying skills may be insufficient [13]. The initial step before implementing any action is to evaluate the level of CTS; hence, a test instrument is needed to assess the level of CTS [34], [35].…”
Section: Language Accuracymentioning
confidence: 99%
“…Therefore, improving these skills is of high urgency, as relying on technology without mastering its underlying skills may be insufficient [13]. The initial step before implementing any action is to evaluate the level of CTS; hence, a test instrument is needed to assess the level of CTS [34], [35].…”
Section: Language Accuracymentioning
confidence: 99%
“…Furthermore, significant correlations between computational thinking and critical thinking, as well as pre-service teachers' modeling skills, were reported in [12,13], where it was found that the fundamental concepts of CT promoted, organized, and structured English writing; increased students' writing motivation; and reduced their writing anxiety. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the authors of [16] provided a framework for social studies teachers regarding the integration of CT into K-12 classrooms. Another study explored the incorporation of CT into English writing instruction [13]. In addition, in [20], the authors designed and implemented computational thinking activities for mathematics students.…”
Section: Introductionmentioning
confidence: 99%